New sex dependent normal limits of the signal averaged electrocardiogram. Issue 2 (August 1994) - Yang, T F; Macfarlane, P W
Abstract : BACKGROUND–An earlier study of 1555 normal 12 lead electrocardiograms has shown that the mean QRS duration in men is 8 ms longer than in women. OBJECTIVE–To establish the sex related normal limits of the signal averaged electrocardiogram. PEOPLE–195 people (160 men and 35 women aged 40 to 69) with normal clinical history, physical examination, 12 lead electrocardiogram, and echocardiogram were recruited for this study. METHODS–Signal averaged electrocardiograms were recorded by the Arrhythmia Research Technology 1200 EPX machine and analysed twice with bidirectional Butterworth filters with frequency ranges of 25-250 Hz and 40-250 Hz. Three time domain parameters of the QRS vector magnitude, namely filtered total QRS duration, duration of low amplitude signals under 40 microV (LAS40), and root mean square voltage of the last 40 ms (RMS40), were evaluated. RESULTS–There were significant differences between the two sexes in QRS duration (mean (95% confidence interval (95% CI) (8.0 (3.1 to 13.0) ms, t = 3.29, degrees of freedom = 41, p = 0.0021 with the 25-250Hz filter; mean (95% CI) 10.2 (6.9 to 13.5) ms, t = 6.26, degrees of freedom = 53, p < 0.0001 with the 40-250Hz filter)) and in body surface area (mean (95% CI) 0.26 (0.21 to 0.31) m2, t = 10.63, degrees of freedom = 57). There was no significant correlation between age and QRS duration, LAS40, or RMS40, but there was a highly significant correlation between body surface area and QRS duration (correlation coefficient = 0.396, p < 0.0005) and RMS40 (correlation coefficient = -0.159, p < 0.025). Current sex independent criteria defining ventricular late potentials as the presence of any two of QRS duration > 114 ms, LAS40 > 38 ms, RMS40 < 20 microV, give a specificity of 85% for men and 91% for women in this normal population. RECOMMENDATIONS–Ventricular late potentials should be regarded as present when (a) QRS duration exceeds 114 ms in men or 104 ms in women and (b) either LAS40 > 38 ms or RMS40 < 20 microV. This gives a specificity of 97% in men and 100% in women in the population studied.